2011
DOI: 10.1002/hep.24058
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ITPA polymorphisms on decreases of hemoglobin during treatment with pegylated interferon, ribavirin, and telaprevir

Abstract: Polymorphisms of the inosine triphosphatase (ITPA) gene influence anemia during pegylated interferon (PEG-IFN) and ribavirin (RBV) therapy, but their effects during triple therapy with PEG-IFN, RBV, and telaprevir are not known. Triple therapy for 12 weeks, followed by PEG-IFN and RBV for 12 weeks, was given to 49 patients with RBV-sensitive (CC at rs1127354) and 12 with RBV-resistant (CA/AA) ITPA genotypes who had been infected with hepatitis C virus (HCV) of genotype 1. Decreases in hemoglobin levels were gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
94
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(105 citation statements)
references
References 28 publications
(54 reference statements)
10
94
1
Order By: Relevance
“…Studies have shown that polymorphisms of the ITPA gene cause a deficiency of this enzyme resulting in decreased incidence of anemia during treatment of HCV with RBV and decreased need for RBV dose reduction [12]. A study by Suzuki et al [13] looked at how the ITPA polymorphism impacted hemoglobin levels on triple therapy with telaprevir in Japanese patients, and found that there was a protective effect of the ITPA polymorphisms from patients with RBV induced hemolysis. In our study, we did not have the appropriate resources to test for the ITPA polymorphism and therefore were not able to account for this confounding effect.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that polymorphisms of the ITPA gene cause a deficiency of this enzyme resulting in decreased incidence of anemia during treatment of HCV with RBV and decreased need for RBV dose reduction [12]. A study by Suzuki et al [13] looked at how the ITPA polymorphism impacted hemoglobin levels on triple therapy with telaprevir in Japanese patients, and found that there was a protective effect of the ITPA polymorphisms from patients with RBV induced hemolysis. In our study, we did not have the appropriate resources to test for the ITPA polymorphism and therefore were not able to account for this confounding effect.…”
Section: Discussionmentioning
confidence: 99%
“…In this setting, two Japanese studies have shown that ITPA polymorphisms are still able to influence hemoglobin levels during triple HCV therapy (7,30).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reproducibly identified polymorphic variation of the ITPA gene leading to enzymatic ITPA deficiency as a major determinant of RBV induced hemolytic anemia [26][27][28][29]. ITPA deficiency results from two SNPs rs1127354…”
Section: Discussionmentioning
confidence: 99%